No Difference Between Latiglutenase and Placebo in Reducing Villous Atrophy or Improving Symptoms in Patients With Symptomatic Celiac Disease - Murray, Joseph A.; Kelly, Ciarán P.; Green, Peter H.R.; Marcantonio, Annette; Wu, Tsung-Teh; Mäki, Markku; Adelman, Daniel C.; Ansari, S.; Ayub, K.; Basile, A.; Behrend, C.; Bercik, P.; et al. (Gastroenterology (New York, N.Y. 1943), 2017)
Gluten ingestion leads to symptoms and small intestinal mucosal injury in patients with celiac disease. The only option is the strict lifelong exclusion of dietary gluten, which is difficult to accomplish. Many patients following a gluten-free diet continue to have symptoms and have small intestinal mucosal injury. Nondietary therapies are needed. We performed a phase 2 study of the ability of latiglutenase, an orally administered mixture of 2 recombinant gluten-targeting proteases, to reduce mucosal morphometric measures in biopsy specimens from patients with celiac disease. We performed a double-blind, placebo-controlled, dose-ranging study to assess the efficacy and safety of latiglutenase in 494 patients with celiac disease (with moderate or severe symptoms) in North America and Europe, from August 2013 until December 2014. Participants reported following a gluten-free diet for at least 1 year before the study began. Patients with documented moderate or severe symptoms and villous atrophy (villous height:crypt depth ratio of ≤2.0) were assigned randomly to groups given placebo or 100, 300, 450, 600, or 900 mg latiglutenase daily for 12 or 24 weeks. Subjects completed the Celiac Disease Symptom Diary each day for 28 days and underwent an upper gastrointestinal endoscopy with duodenal biopsy of the distal duodenum at baseline and at weeks 12 and 24. The primary end point was a change in the villous height:crypt depth ratio. Secondary end points included numbers of intraepithelial lymphocytes, serology test results (for levels of antibodies against tissue transglutaminase-2 and deamidated gliadin peptide), symptom frequencies, and safety. In a modified intent-to-treat population, there were no differences between latiglutenase and placebo groups in change from baseline in villous height:crypt depth ratio, numbers of intraepithelial lymphocytes, or serologic markers of celiac disease. All groups had significant improvements in histologic and symptom scores. In a phase 2 study of patients with symptomatic celiac disease and histologic evidence of significant duodenal mucosal injury, latiglutenase did not improve histologic and symptom scores when compared with placebo. There were no significant differences in change from baseline between groups. ClinicalTrials.gov no: NCT01917630.